Analisis Penyajian PSAK 101 Pada Laporan Keuangan PT. BPRS Al Washliyah - Sari, Riska Dwi; Sitorus, Eva Afrilisa; Handayani, Nisah (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
The problem that occurs in this study is how a PSAk 101 made in a financial statement of PT. SRB to WASHLIYAH. The purpose of this study is to see how many banks that meet the PSAK 103 report in the presentation of the financial statements of PT. SRB TO WASHLIYAH. This study includes an example of a field study using qualitative methods. Which means that this study was conducted by conducting an analysis related to the submission of financial statements from PT. SRB AL WASHLIYAH and PSAK 101, by correlating Islamic financial reporting. Used to make this report is a secondary data source that beruapa financial transaction data that has been provided by PT. SRB TO WASLIYAH. This study itself shows a result that PT BPRS Al WASHLIYAH does not fully disclose PSAK 101 in the financial statements because PT. there are still differences in the presentation of the financial statements of SRB Al WASHLIYAH between the financial statements of PT.SRB AL WASHLIYAH and PSAK 101 regarding the intermediary reporting of a Sharia financial report which for example is PT.SRB Al WASHLIYAH has not disclosed Murabaha's marginal profit on beracana or notes to the financial statements, but we can know from the daily Balance Sheet report that PT.SRB prepares PSAK 101 situation, to make a Sharia financial report.